Simulating moderate altitude using normobaric hypoxia with commercially available hypoxic gas generators - Pedlar, C. R.; Howatson, G.; Whyte, G. P.; Godfrey, T. J.; Macutkiewicz, D. (High Altitude Medicine & Biology, 2005)
Technology designed to deliver normobaric hypoxic gas mixtures via nitrogen dilution is now widely available from several companies worldwide. Hypoxico® HYP-100 is one such unit and is designed to deliver hypoxic gas mixtures simulating a moderate altitude environment. They are commercially available for research, athletic training, and preacclimatization applications (sleep and exercise) and have been referenced in the literature (Kolb et al., 2004; Wilbur, 2001; Wilber 2004). We have used these units during a preacclimatization study with elite winter biathletes (Whyte et al., 2002) and also in examining the effects of a hypoxic tent system on markers of sleep quality (Pedlar et al., 2005). The HYP-100 units are designed to deliver 100 L/min 1 of hypoxic gas ( 14.5% FIO2), which is assumed to be adequate for a single-person sleeping environment. Multiple units can be used to create an exercise environment. During our recent sleep investigation (Pedlar et al., 2005), concern was raised regarding the efficacy of the units to adequately flush residual air (particularly CO2) from the tent and maintain consistent conditions, the primary danger being the potential for hypercapnia in an enclosed environment. In response to these concerns, we have since measured the output volume (L/min 1) and gas mixture composition (fraction of O2 and fraction of CO2) from eight units over an 8-h period using Douglas Bags. We sampled at the following time points: 0.5, 30, 60, 120, 180, 240, 300, and 480 min. The trials were conducted in a large, well-ventilated laboratory at sea level. The flow rate dial on each unit was set at its maximum level. Table 1 summarizes the output of the units and the ambient conditions of the laboratory. Although the consistency of the units over time was good (see Fig. 1), the absolute output volume falls on average 30.4% short of the 100 L/min 1 described by the manufacturer. This must be considered in the various applications of these units when calculating the output volume required to displace the air within an enclosure. Clearly, the volume of flow required during sleep is considerably different from that required during exercise. For example, an elite heavyweight male rower during heavy exercise could ventilate more than 200 L/min 1, consuming more than 4 L/min 1 of oxygen and producing equal quantities of carbon dioxide that would need to be displaced. Further examination of normobaric hypoxic environments designed for this purpose is warranted, and verification of the performance of the technology is crucial.